Low-frequency noise analysis on asymmetric damage and self-recovery behaviors of ZnSnO thin-film transistors under hot carrier stress - Wonjun Shin; Ji Ye Lee; Jangsaeng Kim; Sang Yeol Lee; Sung-Tae Lee (Discover Nano)
Abstract The need for understanding the low-frequency noise (LFN) of metal oxide semiconductor thin-film transistors (TFTs) is increasing owing to the substantial effects of LFN in various circuit applications. A focal point of inquiry pertains to the examination of LFN amidst bias stress conditions, known to compromise TFT reliability. In this study, we investigate the effects of hot carrier stress (HCS) on zinc tin oxide (ZTO) TFTs by low-frequency noise (LFN) analysis. Asymmetric damage caused by HCS is analyzed by measuring the power spectral density at the source and drain sides. The excess noise generated by the HCS is analyzed with consideration of trap density of states (DOS). It is revealed that the needle defects are generated during the HCS, significantly affecting the LFN characteristics of the ZTO TFTs. Additionally, we observe a self-recovery behavior in the devices and demonstrate the relevant changes in the LFN characteristics following this phenomenon. This study provides valuable insights into the LFN characteristics of ZTO TFTs under HCS conditions and sheds light on the underlying mechanisms.